Proceso de atención nutricional en paciente femenino de 40 años de edad con hipertensión arterial e hipercolesterolemia. - Aguiar López, Denisse Andreina (2023)
This clinical case is a 40-year-old female patient with a medical diagnosis of hypertension and hypercholesterolemia. Cardiovascular diseases contribute an important risk factor in the increase in morbidity and mortality of people with hypertension and hypercholesterolemia. Objective: To improve the nutritional status of the patient with hypertension and hypercholesterolemia, the nutritional status is evaluated through anthropometric, biochemical, clinical/physical and dietary indicators, the nutritional diagnosis was made, a nutritional plan was intervened according to the needs of the patient prior to obtaining informed consent to start nutritional treatment, follow-up was carried out to monitor the previously evaluated indicators and significant changes were observed in anthropometric, biochemical, clinical/physical and dietary indicators.